2005
DOI: 10.1159/000088593
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Laparoscopic Therapy of Cholecystolithiasis and Common Bile Duct Stones

Abstract: Background: Laparoscopic cholecystectomy (LC) is the standard operation for gallstone disease. The aim of this review was to scrutinize the advantages and benefits of this minimal invasive technique compared to the conventional operation according to the available literature. Regarding the evidence-based medicine criteria, the current status of laparoscopy in the treatment of cholecystolithiasis, cholecystitis and common bile duct stones has been worked out. Methods: A Medline, PubMed, Cochrane search. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 177 publications
(70 reference statements)
1
14
0
3
Order By: Relevance
“…The modulation of the immunological system as well as the inflammatory reaction has been described by many authors [1]. Regardless of the shorter hospital stay and better cosmetic effect for the patients who undergo laparoscopic surgery, this technique is not immune from the consequences of surgical trauma [27][28][29]. Laparoscopic techniques have been continuously improved.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of the immunological system as well as the inflammatory reaction has been described by many authors [1]. Regardless of the shorter hospital stay and better cosmetic effect for the patients who undergo laparoscopic surgery, this technique is not immune from the consequences of surgical trauma [27][28][29]. Laparoscopic techniques have been continuously improved.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy is comparable to open cholecystectomy with regard to mortality and the incidence of complications [23,24], leads to a significantly shorter hospital stay, and is generally preferred as the first-choice surgical procedure (Fig. 1) [25][26][27][28]. It has been reported that 3.6-8% of laparoscopic cholecystectomies are intraoperatively switched to open procedures for a variety of reasons, including technical difficulties, biliary tract damage, anesthesia problems, and device malfunction [29][30][31][32].…”
Section: Commentarymentioning
confidence: 99%
“…These advantages include not only better cosmesis, less postoperative pain, smaller wounds, early return to normal activities, and higher patient satisfaction, but also better illumination and magnification allowing excellent visibility of minute details [1][2][3][4]. Strong enthusiasm for the technique hindered early careful evaluation of this procedure, which was later shown to entail some specific risks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Strong enthusiasm for the technique hindered early careful evaluation of this procedure, which was later shown to entail some specific risks [5]. Nevertheless, LC has been established as the standard treatment for symptomatic gallbladder diseases [1].…”
Section: Introductionmentioning
confidence: 99%